Measurement of the ratio of inclusive cross sections sigma(p(p)over-bar -> Z plus b jet)/sigma(p(p)over-bar -> Z plus jet) at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2005)
Using the data collected with the D0 detector at root s=1.96 TeV, for integrated luminosities of about 180 pb(-1), we have measured the ratio of inclusive cross sections for p(p) over bar -> Z+b jet to p(p) over bar -> Z+jet production. The inclusive Z+b-jet reaction is an important background to searches for the Higgs boson in associated ZH production at the Fermilab Tevatron collider. Our measurement is the first of its kind, and relies on the Z -> e(+)e(-) and Z ->mu(+)mu(-) modes. The combined measurement of the ratio yields 0.021 +/- 0.005 for hadronic jets with transverse momenta p(T)> 20 GeV/c and pseudorapidities vertical bar eta vertical bar < 2.5, consistent with next-to-leading-order predictions of the standard model.